Does intellectual capital affect the venture creation decision in India? - Ahmed Musa Khan; Mohd Yasir Arafat; Mohd Anas Raushan; Imran Saleem; Nawab Ali Khan; Mohd Mohsin Khan (Journal of Innovation and Entrepreneurship, 2019)
Purpose: Although the intellectual capital (IC) has already received much attention from the researchers in the field of innovation performance, there is still a paucity in measuring the role of IC in venture creation. The present study is an attempt to examine the influence of IC on start-ups. Methodology: In this study, a large data set of 3413 respondents from India has been used. The data has been provided by the largest entrepreneurship research project GEM. A logistic regression technique has been applied to measure the influence of IC on entrepreneurial intentions. Findings: It has been found that the components of intellectual capital, i.e., knowledge and skills, entrepreneurial opportunities, knowing other entrepreneurs, business angel, and educational level have a positive and significant impact on the entrepreneurial intentions. Contribution: To the best of our knowledge, it is among the initial studies, which have examined the relationship between intellectual capital and entrepreneurial intentions. Only a few studies have already been done in developing countries like India by using a large data set.
Keywords: 650; Intellectual capital; Entrepreneurial intention; Entrepreneurial opportunities; Knowledge & Skills; Network and educational; Global entrepreneurship monitor; Logistic regression; India